2010
DOI: 10.1111/j.1365-4632.2010.04545.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective open‐label clinical trial of adalimumab for the treatment of hidradenitis suppurativa

Abstract: Our study demonstrated statistically clinical improvement is not observed in the treatment of HS with adalimumab. Future studies using higher doses of adalimumab are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 15 publications
0
88
0
5
Order By: Relevance
“…However, after 12 weeks of treatment no difference could be observed compared with baseline or with placebo. Nonetheless, these studies report on high recurrence rates after discontinuation [75,76]. It has been suggested that a weekly dose is more effective [3].…”
Section: Adalimumabmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after 12 weeks of treatment no difference could be observed compared with baseline or with placebo. Nonetheless, these studies report on high recurrence rates after discontinuation [75,76]. It has been suggested that a weekly dose is more effective [3].…”
Section: Adalimumabmentioning
confidence: 99%
“…Over the years multiple studies followed, reporting different clinical outcomes. Two prospective studies using a dose of 40 mg every other week showed initial improvement [75,76]. However, after 12 weeks of treatment no difference could be observed compared with baseline or with placebo.…”
Section: Adalimumabmentioning
confidence: 99%
“…There are several scoring systems for assessing disease severity (Hurley staging, HS-Physician's Global Assessment [PGA], the modified Sartorius score [MSS], Hidradenitis Suppurativa Severity Index [HSSI]) (Table 1) [16,17,18,19]; however, all of them have some limitations in daily practice [20]. …”
Section: Classification and Severity Assessmentmentioning
confidence: 99%
“…Regarding adalimumab, in both case reports and more extensive studies, an improvement in HS lesions was observed between 4 and 12 weeks of treatment, and the results were maintained for the duration of therapy, despite increasing doses specified in some reports [7,8,9,10,11,12,13,14,15,16,17,18] (data summarized in table 3). Therefore, adalimumab treatment seems to have a favorable outcome in the treatment of HS, with improvement somewhat slower than with infliximab, but maintained over time, with a high safety profile.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Therefore, adalimumab treatment seems to have a favorable outcome in the treatment of HS, with improvement somewhat slower than with infliximab, but maintained over time, with a high safety profile. The main secondary adverse event was edema at the site of injection; other serious adverse effects were exceptional [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Miller et al [20] conducted a double-blind placebo-controlled study which included 15 patients who received adalimumab 80 mg at week 1 and 40 mg eow for 12 weeks; 6 remaining patients were given a placebo.…”
Section: Review and Discussionmentioning
confidence: 99%